Switching dynamics in ferroelectric superlattices - Chew, Khian Hooi; Iwata, M.; Ong, L.H. (Elsevier, 2011)
Dynamics of polarization switching in a superlattice, consisting of alternating ferroelectric and parelectric layers, is studied by the Landau Khalatnikov equation. The dependence of switching time on the dielectric stiffness of the paraelectric layer, interface coupling and layer thicknesses is examined in detail. The spatial distribution of polarizations at different time in switching is illustrated. The results are discussed with those obtained using the model as proposed by Qu et al. [B.D. Qu, W.L. Zhong and R.H. Prince, Phys. Rev. B 55, 11218 (1997)]. Our results show that the two models give a similar qualitative description of switching dynamics. (C) 2010 Elsevier B.V. All rights reserved.